Human CD8+ T lymphocyte subsets that express HLA class I-specific inhibitory receptors represent oligoclonally or monoclonally expanded cell populations. - Mingari, M C (1996)
A small percentage of human T lymphocytes, predominantly CD8+ T cells, express receptors for HLA class 1 molecules of natural killer type (NK-R) that are inhibitory for T-cell antigen receptor (TCR)-mediated functions. In the present study, it is demonstrated that the various NK-R molecules typically expressed by NK cells are also expressed on periheral blood T lymphocytes. These CD3+ NK-R+ cells have a cell surface phenotype typical of memory cells as indicated by the expression of CD45RO and CD29 and by the lack of CD28 and CD45RA. Furthermore, by the combined use of anti-TCR V beta-specific antibodies and a semiquantitative polymerase chain reaction assay, the TCR repertoire in this CD3+ NK-R+ cell subset was found to be skewed; in fact, one or two V beta families were largely represented, and most of the other V beta s were barely detected. In addition, analysis of recombinant clones of the largely represented V beta families demonstrated that these V beta s were oligoclonally or monoclonally expanded.